ปัญหาของการควบคุมภายในของธุรกิจโรงแรมในจังหวัดเชียงใหม่ - นัฐนาถ ยอดชาสุวรรณ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The objective of this independent study was to explore the problems of internal control in hotel business in Chiang Mai Province, according to the internal control concept by the Committee of Sponsoring Organizations of the Treadway Commission (COSO). The COSO internal control concept consists of 5 components as follows: Control Environment, Risk Assessment, Control Activities, Information and Communication and Monitoring. Data were collected by questionnaires with open and close-ended questions given to administrators of four to five stars hotels in Chiang Mai. The researcher classified the problems of internal control into three areas: financial and accounting, rooms control, and food and beverage control. The study found that most of respondents were females aged between 31 and 40 years old, education level of bachelor’s degree, working as managers of finance and accounting department in four stars hotel with 6-10 years of work experience. The results showed that the problems of internal control in hotel business were overall at a low level. Considering the details of each problem, it was found that in terms of control environment, the most recurring problems were inadequate staff, not enough training, and unclear policies. As for risk assessment, lack of knowledge and understanding in the objective of risk assessment was the biggest problem. As for the control activities component, recurring problems were lack of cooperation and non-compliance with defined internal control policy. In regards to information and communication, the problems were internal communication problems and problems with software and equipment. As for monitoring, there was a lack of officers responsible to follow up directly, continuously monitor, and evaluate. The study revealed the most recurring problems of internal control in hotel business in Chiang Mai. The results of the study can be taken as a guideline to improve and applied in planning of internal control systems with appropriate for hotel business. For further effectiveness and efficiency of operations, reliability of financial reporting and compliance with applicable laws and regulations.